Bailing out the food banks? Hunger relief, food waste, and crisis in Central Appalachia. (March 2018) - Lohnes, Joshua; Wilson, Bradley
In 2015, West Virginia's flagship food bank confronted a financial crisis that threatened to cut off the supply of emergency food to some 600 agencies serving 300, 000 people a month. Focusing on this crisis, we explore the evolution of charitable food networks across the United States with a particular focus on the role of food banking within agro-industrial supply chains. Drawing on a three year institutional ethnography of West Virginia's food banking economy, we analyze the transition from producer to buyer driven supply chains in a network that is dependent on charitable giving and affective labor to process surplus foods and revalue obsolete corporate inventories. We argue that food banks and their affiliate agencies have become key institutions within a vast food destruction network increasingly serving the needs of large food firms. While food banks and their affiliate agencies provide tax relief for food corporations and offer a highly efficient vent for state subsidized and corporate food waste, they are primarily funded by community-based organizations who are themselves stretched thin by economic crises within their own locales. The entrenchment and evolution of the food waste qua hunger relief circuit is producing new tensions in a network that is conflicted over whom they are ultimately working for, and sheds light on the paradox of hunger relief in the 21st-century.